MEWUJUDKAN KESADARAN MASYARAKAT AKAN KEBERSIHAN LINGKUNGAN UNTUK MENGHADAPI NEW NORMAL DI KELURAHAN KEBUN LADA BINJAI - M Danang Pa; Agus Tri Anto; Muhammad Rizky; Salma Rozana (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
This project aims to realize community awareness of environmental cleanliness to deal with new normal and provide direct experience to students in identifying and dealing with social problems, as well as increasing environmental awareness in the community. The methods used include observation, interviews, documentation, and deliberation with the local community. Activities consisted of environmental counseling, mutual cooperation activities to clean public facilities, and data collection of residents. The results showed that the program ran smoothly thanks to the enthusiasm and support of the local community, although there were obstacles such as time constraints and schedule adjustments. The evaluation showed success in increasing community participation.